Performance Evaluation Of Shankarnagar Water User’s Committee, Rupandehi, Nepal - Acharya, Shishir; Dahal, Khetraj; Dhakal, Sujeet; Mainali, Sita Ghimire (International Journal on Engineering Technology, 2026)
National coverage of basic water supply and sanitation in Nepal improved significantly between 2014 and 2019, increasing from 83.59% to 87.88% for water supply and from 72.22% to 98.32% for sanitation. However, many completed water supply schemes face functionality challenges: only 28.14% are functioning well, while the rest require varying levels of repair, rehabilitation, or reconstruction. This study assesses the performance of the Shankarnagar Water Supply Consumers and Sanitation Association (SWSCSA) as a representative water utility. Performance was evaluated in terms of physical condition, functionality, quality of service, and operational and financial management. Primary data were collected through household surveys, key informant interviews, focus group discussions, site visits, and water quality testing, while secondary data were obtained from official documents, reports, and published literature. Key performance indicators were grouped into three categories: quality of service, operational performance, and financial performance. Quality of service indicators included water quality, quantity, and affordability. Operational performance was assessed using metering ratio, staff productivity, energy consumption, and non-revenue water (NRW). Financial performance was evaluated using the cost recovery ratio (CRR), maintenance cost as a proportion of operating cost, and revenue collection ratio (RCR).